Association between Lifestyle Habits and Major Depression in Patients Attending Psychiatric Clinics in Sana’a City, Yemen: A Case-Control Study - Essam H. Al-Safadi; Adel A. Alemad; Ahmed S. Hudna (University of Science and Technology, Sana’a, Yemen, 2024)
Background: Depression is a serious mental disorder and is ranked as the fourth leading cause of disease burden worldwide, which can be multifactorial with unclear etiology. Therefore, this study assessed the association between certain lifestyle habits and depression among psychiatric patients in Sana’a city, Yemen. Methods: An unmatched case-control study was conducted in October and November 2019 at Al-Amal Hospital for Psychiatric Diseases and outpatient clinics of the University of Science and Technology Hospital (USTH) in Sana’a. Thirty patients aged 18–65 years, with a mean age of 31.1 ± 10.4 years, who were diagnosed with major or unipolar depression for the first time in the past three months were conveniently selected as cases, while 90 adult subjects, with a mean age of 30.9 ± 10.5 years, were conveniently selected as non-depressed controls from various USTH clinics other than the psychiatric clinic during the study period. Data on sociodemographic characteristics and lifestyle habits were collected using a structured questionnaire. Univariate analysis using the chi-square or Fisher’s exact test was used to test the association between lifestyle habits and depression, with a confidence level of less than 0.05. Results: There was no statistically significant association between depression among patients attending psychiatric clinics and current smoking status (OR = 0.9, 95% CI: 0.29–2.57; P = 0.785), khat chewing (OR = 1.0, 95% CI: 0.41–2.25; P = 0.913), or the frequency of khat chewing (OR = 0.8, 95% CI: 0.21–3.26; P = 0.932). Coffee drinking was not significantly associated with depression (OR = 1.1, 95% CI: 0.50–2.62; P = 0.750), while infrequent drinking of red tea was significantly associated with depression among patients compared to controls (OR = 16.8, 95% CI: 6.14–45.73; P <0.001). On the other hand, no significant association was found between hours of sleep per day and depression (OR = 1.7, 95% CI: 0.71–3.87; P = 0.245). However, sedentary lifestyle was significantly associated with depression among psychiatric patients compared to controls (OR = 5.2, 95% CI: 2.15–12.7; P <0.001). Conclusion: Drinking red tea and regular exercise may help reduce depression in psychiatric patients with depression. By encouraging the integration of red tea consumption and regular exercise into the daily routine of Yemeni patients with depression, healthcare providers can support the mental health and well-being of this population.